Penerapan Metode ABC dalam Perbaikan Tata Letak Gudang Bahan Baku di PT. Alfa Polimer Indonesia - Nabila Fazrin; Eka Ludiya (Penerbit Goodwood, 2023)
Purpose: PT. Alfa Polimer Indonesia are the company who produce a water-based adhesive and speciality chemical manufacture that focused on various industry application with the main raw material is PVA Series. Based on observation and interviews to PVA Series raw material warehouse the information was obtained that the layout of PVA Series raw material warehouse was not properly placed, the irregular range between pallets getting effect delayed operational process in raw material warehouse and delivery of raw materials to the production department. The main aim on this research are to know and defines how to apply the ABC analysis method to the layout of the raw material warehouse at PT. Alfa Polimer Indonesia. Methodology: This research using the descriptive qualitative research and the purposive sampling with using the data analysis technique that are data reduction, data display and conclusion. And then using the source triangulation, technique triangulation and time triangulation as the data collection techniques. Results: The result obtained after processing data are the improvement effort for the layout of PVA Series raw material warehouse with using the ABC analysis method will be increases the storage capacity in the mount of 71,42 percent.